Congenital acute myeloid leukemia: challenges and lessons. A 15-year experience from the UK. Issue 3 (23rd February 2021) - Green, Katherine; Tandon, Sneha; Ahmed, Mansur; Toscano, Wanda; O'Connor, David; Ancliff, Philip; Vora, Ajay; Bartram, Jack; Samarasinghe, Sujith; Ghorashian, Sara; Pavasovic, Vesna; Rao, Anupama
Abstract: Congenital Acute Myeloid leukemia (CAML) is a rare leukemia diagnosed within the first 28 days of life. Dismal survival rates of approximately 25% at two years from diagnosis have not improved despite multiple treatment protocols, and there lacks international consensus for optimal management of these vulnerable patients. We report a retrospective analysis of our fifteen-year experience from a large UK tertiary pediatric center, focusing on treatment modalities and outcomes, including late therapeutic toxicities. To our knowledge, this is the first UK series of congenital leukemia patients reported. Twelve patients with a median age of 16.4 days (1–60) were diagnosed with CAML in fifteen years. All patients presented unwell; 92% demonstrating skin involvement. 10 (83%) received chemotherapy; with 1 death at presentation and 1 spontaneous remission. 5 (42%) received subsequent stem cell transplant. Only 4 (33%) remain alive, with 5 (42%) dying in disease remission with treatment-related mortality. Documented cardiotoxicity was observed in 3 (25%) patients, with a further 2 (17%) suspected but not receiving postmortem. Treatment of congenital AML raises challenging diagnostic, therapeutic and ethical questions and requires multi-center, international collaboration to see improvements.